Forensic Document Examination in the 21st Century - Angel, Miriam; Seaman Kelly, Jan (CRC Press, 2021)
Forensic Document Examination in the 21st Century presents the latest techniques on current issues and methods in forensic document examination. Due to recent advances in technology, including digital documents and signatures, enhanced printing and photocopying capabilities, and more, there is a great need for an up-to-date, in-depth reference. The examination of documents can include comparison of handwriting, detection of alterations or photocopier and computer manipulation, restoration or decipherment of erased and obliterated writing; visualization of latent impressions, the identification of printing processes; and differentiation of inks. Computer-generated documents are prevalent, and electronically-captured signatures are becoming widespread now, meaning an understanding of the technology and new validated techniques and methods of document examination are more crucial than ever to the reliability of forensic opinions. Section I of the book discusses forensic document examination's place in the larger world of forensic science, investigations, and the court-addressing academic and scientific developments in the field. Section II covers current handwriting theory, factors to be considered in the evaluation process, and methods of handwriting analysis. Section III includes various topics related to technology or specialized examinations. This includes utilizing technology to assess evidence in the form of computer-generated documents or electronic signatures, using instrumentation for analyzing evidence, and utilizing technology to enhance evidence to demonstrate findings in court. Chapters demonstrate the application of logical reasoning, sound practice, and transparency validate and strengthen reporting and evaluations. Forensic Document Examination in the 21st Century includes the latest research on the subject with contributions from leading experts writing on their various areas of expertise. The book will serve as an essential resource for forensic document examiners, trainees, expert witnesses, and those in the forensic, criminal justice, and legal communities who use the services of expert document examiners and witnesses, Defines updated standards for training and various examination methods to detect fraudulent documents, including computer-generated and digital documents. Describes the examination of electronic signatures and introduces experiments done to validate those methods. Explains Bayes Theorem and how the likelihood ratio can be used to interpret and evaluate evidence. Details how human factors such as bias could introduce errors and present means to minimize those errors. Outlines expert requirements to effectively present evidence in court and in Daubert hearings, including how to utilize technology to better visualize and enhance demonstration of evidence.